Dinamika Stres pada Anak Muda Generasi Z: Studi Literatur dan Implementasi Teknik Konseling Terintegrasi - Ricard Lieberth; Juliana Hindradjat (Universitas Malahayati Lampung, 2026)
ABSTRACT Generation Z, comprising individuals born between 1995 and 2012, represents the age group most closely intertwined with rapid technological advancement and shifting social dynamics. Numerous studies indicate that this generation experiences higher levels of stress compared to previous cohorts, influenced by academic pressure, digital–social demands, economic instability, and developmental identity challenges. This study employs a Systematic Literature Review (SLR) of 25 indexed scholarly articles to analyze the dynamics of stress among Generation Z youth and identify evidence-based counseling interventions proven effective in managing these challenges. The findings reveal that stress in Generation Z is multidimensional, encompassing cognitive, emotional, social, and behavioral aspects that are shaped by intensive social media use, social comparison, sleep disturbances, and academic burdens. Counseling techniques such as Cognitive Behavioral Therapy (CBT), Mindfulness-Based Interventions (MBI), Motivational Interviewing (MI), and empathic confrontation were found to be effective in enhancing emotional regulation and building resilience. This article offers a comprehensive understanding of the root causes of stress in Generation Z, its implications for mental health, and relevant intervention strategies for counselors, educators, and mental health practitioners in Indonesia. Keywords: Stress, Generation Z, Mental Health, Counseling, SLR ABSTRAK Generasi Z, yang mencakup individu kelahiran 1995–2012, merupakan kelompok usia yang paling erat dengan perkembangan teknologi digital serta perubahan sosial yang cepat. Berbagai penelitian menunjukkan bahwa kelompok usia ini mengalami tingkat stres lebih tinggi dibanding generasi sebelumnya, yang dipengaruhi oleh tekanan akademik, tuntutan sosial-digital, ketidakstabilan ekonomi, dan dinamika perkembangan identitas. Penelitian ini menggunakan pendekatan Systematic Literature Review (SLR) terhadap 25 artikel ilmiah terindeks untuk menganalisis dinamika stres pada anak muda Generasi Z serta mengidentifikasi intervensi konseling berbasis bukti yang terbukti efektif. Hasil analisis menunjukkan bahwa stres pada Generasi Z bersifat multidimensional, mencakup aspek kognitif, emosional, sosial, dan perilaku yang dipengaruhi oleh intensitas penggunaan media sosial, perbandingan sosial, gangguan tidur, dan beban akademik. Teknik konseling seperti Cognitive Behavioral Therapy (CBT), Mindfulness-Based Interventions(MBI), Motivational Interviewing (MI), dan teknik konfrontasi empatik ditemukan efektif dalam membantu regulasi emosi dan pengembangan resiliensi. Artikel ini memberikan pemahaman komprehensif tentang penyebab stres pada Generasi Z, dampaknya terhadap kesehatan mental, serta strategi penanganan yang relevan bagi konselor, pendidik, dan praktisi kesehatan mental di Indonesia. Kata Kunci: Stres, Generasi Z, Kesehatan Mental, Konseling, SLR.